Pekojan: Image of an Arab Kampong during XVIII to XIX Centuries Batavia - Johan Wahyudi; Dien Madjid (Insaniyat : Journal of Islam and Humanities, 2019)
This study discusses the social dynamics of a kampong in Batavia during XVIII to XIX centuries. Pekojan has already emerged as the center of commerce for Arabs and Muslim Indians community since the 16th century. By the eighteenth century, many Arab immigrants from Hadramawt (Southern Yemen) settled here. Its initial landscape can be traced by the theory of the coming of Islam in the Archipelago. One of the theories says that it was driven by international trade by the Arabs, which also carried Islam along with them. The Hadramis went through the naval journey passing the Indian Ocean to the Malaka Strait. They stopped over in Singapore then went on to Batavia, especially Pekojan. This study found Pekojan became a place where Arab culture and ideas were constructed yet negotiated within a local context. There prominent ulamas, merchants, writers, educators, the initiators of independence, the benefactors, and artists socialized under close racial surveillance of the Dutch East Indies government.